O papel do migrante como sujeito da genealogia e dinâmica urbana do município de Rorainópolis - Roraima - Oliveira, Roniel Vitor de (2014)
This research examines the role of the migrant as a subject of genealogy and urban dynamics in the northern city of Rorainópolis Amazon, Amazon last frontier. The research covers the time interval from the 1970s to the year 2013. In this way, the research techniques used were bibliographic, documentary and photographic analyzes interviews, questionnaires and in situ observations. In Roraima, Rorainopolis city that emerged in this part of the Amazon in the late 1970s , the political consequences in human and territorial occupation in Amazonia directed by the central government . Occupation policies that had migration as a central element, since the conception of the territory was associated with a human occupation, disregarding the characteristics of the forest and an existing population. Therefore, the military government effected actions, such as building roads and settlement projects, in order to occupy and exploit economically regions considered demographic gaps. In this situation, lying south of the State of Roraima, trimming this research, when using the municipality as Rorainópolis element analysis in order to understand the role of migrants in genealogy and dynamics of this urban area? Based on this assumption, a migratory flow is directed to that portion of Roraima territory and constitute begins in the late 1970s, a small cluster margins of the BR - 174 highway. Also in 1979 the brand Settlement Project Managed PAD- Anaua installation, marking the consolidation of the urban core of embryonic Rorainopolis. The national installs its headquarters in this space, and from that moment the small cluster becomes known as Village of INCRA, from then on, this core embryonic received large urban population growth due to migration flows intended for this portion South of the State of Roraima, during the late 1970s, which followed in the 1980s and 1990s. In this trajectory, another element that marks the history of this place was in 1995, when the village known INCRA win city status with the name of Rorainopolis with the political emancipation of the municipality of the same name. In this context, the urban core Rorainopolis, its urban sprawl is happening, marked by a lack of basic infrastructure, equipment and adequate urban services, and in this sense, consolidating the loss of quality of life of its residents.